(untitled) (Physical Education, Health and Social Sciences, 2026)
Late blight, caused by the hemibiotrophic oomycete Phytophthora infestans, remains the most destructive disease of potato (Solanum tuberosum L.), historically responsible for the Irish Potato Famine and currently inflicting global economic losses of approximately 12 billion annually through direct yield destruction and intensive fungicide use. This comprehensive review synthesizes recent advances in understanding host–pathogen interactions, molecular diagnostics, and novel breeding strategies aimed at achieving durable, broad-spectrum resistance. The pathogen’s sophisticated effector arsenal (RXLR and Crinkler families) and rapid evolutionary adaptability are countered by potato NLR (nucleotide-binding leucine-rich repeat) resistance (Rpi) genes sourced from diverse wild Solanum relatives. Cutting-edge diagnostic tools including qPCR, ddPCR, LAMP, RPA, and NGS-based RenSeq/SMRT-AgRenSeq enable rapid, field-deployable early detection of P. infestans and high-throughput mining of functional R genes. Novel breeding approaches encompass marker-assisted selection (MAS), genomic selection (GS), gene pyramiding, cisgenesis, and precise CRISPR/Cas9-mediated knockout of susceptibility (S) genes such as StDMR6-1, StNRL1, and StDND1, which confer multi-pathogen resistance without yield penalties. Host-induced gene silencing (HIGS/RNAi) further augments protection by targeting essential pathogen genes. Integration with precision agriculture technologies spore trapping, AI-powered image recognition (CNNs achieving >97% accuracy), and digital-twin modeling facilitates proactive, reduced-input management. Global field trials of 3R-gene stacked varieties have demonstrated complete resistance under high disease pressure, delivering substantial socio-economic benefits. Collectively, the synergistic deployment of these molecular and digital tools marks a paradigm shift from reactive chemical control to sustainable, resilient potato production capable of withstanding evolving pathogen populations and climate pressures.